3D Printing Unique Nanoclay‐Incorporated Double‐Network Hydrogels for Construction of Complex Tissue Engineering Scaffolds. Issue 11 (5th May 2021) - Guo, Zhongwei; Dong, Lina; Xia, Jingjing; Mi, Shengli; Sun, Wei
Abstract: The development of new biomaterial inks with good structural formability and mechanical strength is critical to the fabrication of 3D tissue engineering scaffolds. For extrusion‐based 3D printing, the resulting 3D constructs are essentially a sequential assembly of 1D filaments into 3D constructs. Inspired by this process, this paper reports the recent study on 3D printing of nanoclay‐incorporated double‐network (NIDN) hydrogels for the fabrication of 1D filaments and 3D constructs without extra assistance of support bath. The frequently used "house‐of‐cards" architectures formed by nanoclay are disintegrated in the NIDN hydrogels. However, nanoclay can act as physical crosslinkers to interact with polymer chains of methacrylated hyaluronic acid (HAMA) and alginate (Alg), which endows the hydrogel precursors with good structural formability. Various straight filaments, spring‐like loops, and complex 3D constructs with high shape‐fidelity and good mechanical strength are fabricated successfully. In addition, the NIDN hydrogel system can easily be transformed into a new type of magnetic responsive hydrogel used for 3D printing. The NIDN hydrogels also supported the growth of bone marrow mesenchymal stem cells and displayed potential calvarial defect repair functions. Abstract : In this work, a novel self‐supporting, self‐recovery, and 3D printable nanoclay‐incorporated double‐network (NIDN) hydrogel biomaterial ink is developed. Various straight filaments, spring‐like loops, and complex 3D constructs with high shape‐fidelity and good mechanical strength are fabricated successfully. Furthermore, the NIDN hydrogels also exhibit good biocompatibility and display potential calvarial defect repair functions.